(untitled) (Conversatoria Linguistica, 2019)
The article is an attempt to analyze a fairy tale (magical) written by a student with difficulties in reading and writing. The work is a fragment of a wider study of narrative texts of people with linguistic disorders resulting mainly from the insufficient language and/or communicational skills (Grabias 2012). The main question stated in this article concerns the correlation between the language skills and the narrative efficiency, between the high and low skills in both areas. The analysis of the language skills in the student’s text shows that the level of the linguistic competence is insufficient. The student almost does not use punctuation, he makes numerous spelling mistakes and uses stereotypical language constructions. Nevertheless, the student’s text, despite the abovementioned linguistic defects, is coherent, and proves the ability to use superstructures in the understanding of Labov. It also proves the student’s ability to build the superior sense of the story through the appropriate functionalization of the particular motifs. In view of the above, it seems to me that in the case of a significant difference between the language and narrative skills exposed on a larger number of the research samples, it would be possible to hypothesize on the various sources of the mechanisms of the abovementioned abilities.